Perbaikan Kualitas Semai Tusam Pasca Sapih melalui Aplikasi Trichoderma Formulasi Pupuk Lambat Tersedia dan Substitusi Media Tumbuh - S. M. Widyastuti; Sumardi Sumardi; N. Estikasari (Jurnal Perlindungan Tanaman Indonesia, 2004)
The experiment was conducted based on damage developed on pine nursery, which killed pine seedlings at a significant number. The damage started on 4 month-aged seedlings indicated by yellowing of needle, followed by development of brown spots on the needle and subsequently could kill the transplanted seedlings. Application of formulated Trichoderma and slow released fertilizer was aimed to avoid the initial symptom, which was assumed due to nutrient deficiency and to control the subsequent infection and disease development. Substitution of composting materials and rice hull into regular growth medium as the main treatment resulted 4 combination treatments. The results indicated that despite all treatments showed significant effects, application of Trichoderma together with slow released fertilizer (PJTJ) on regular medium (medium IV) gave the highest growth increment performance and suppression of damage in seedlings.